2019
DOI: 10.1111/maps.13236
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of carbonaceous materials in Hayabusa‐returned samples to understand their origin

Abstract: Carbonaceous materials in the sample catcher of the Hayabusa spacecraft were assigned as category 3 particles. We investigated the category 3 particles with a suite of in situ microanalytical methods. Possible contaminants collected from the cleanrooms of the spacecraft assembly and extraterrestrial sample curation center (ESCuC) were also analyzed in the same manner as category 3 particles for comparison. Our data were integrated with those of the preliminary examination team for category 3 particles. Possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Notably, these characteristics are not definitive, and further analyses are required to identify these compounds. To obtain the accurate evaluation of the sample profile, we need multi-technical approach including the nondestructive analysis (e.g., IR and Raman), destructive analysis (e.g., GC/MS), and comprehensive working flow (e.g., Uesugi et al 2014Uesugi et al , 2019.…”
Section: Ir and Raman Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these characteristics are not definitive, and further analyses are required to identify these compounds. To obtain the accurate evaluation of the sample profile, we need multi-technical approach including the nondestructive analysis (e.g., IR and Raman), destructive analysis (e.g., GC/MS), and comprehensive working flow (e.g., Uesugi et al 2014Uesugi et al , 2019.…”
Section: Ir and Raman Spectramentioning
confidence: 99%
“…We also note that we have previously studied the analytical pathways in Hayabusa based on an investigation of category 3 carbonaceous particles, which indicated analogous potential contaminants that could be observed throughout the sampling processes of Hayabusa2 (e.g., Ito et al 2014;Yabuta et al 2014;Uesugi et al 2014;Naraoka et al 2015;Kitajima et al 2015). To exclude the potential artifact of any carbonaceous materials, categorizing the sample grain is one of rational ways in regard to quality control and quality assurance, likewise the procedure of Itokawa-returned sample in the Hayabusa mission (e.g., Uesugi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Quality control for the sample process, including in ground-based procedures, is an important issue for sample return missions. The ESCuC (the Extraterrestrial Sample Curation Center) in the ISAS/JAXA facility (Yada et al, 2014;Uesugi et al, 2019) was assessed by an interlaboratory evaluation, and Sugahara et al (2018) reported an assessment of the clean room at ISAS/JAXA, which is intended to be used in the processing Hayabusa2 samples (cf. assessment on the OSIRIS-REx mission; Dworkin et al, 2017).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Therefore, concerning the in situ analysis of organics and volatiles and sample size, these samples require even more careful handling and proper analytical sequencing without terrestrial contamination and sample damage in texture, morphology, isotopic fractionation, major and trace element abundances (e.g., Ito Uesugi et al (2014a) pointed out problems related to sample handling/preparation processes (lost and/or broken) and sample damage (crystal/molecule structural changes, disturbance of elements and isotopic fractionation) of the Itokawa carbonaceous particles (also known as Category 3 organic materials) in electron and ion beam analyses (i.e., TEM and SIMS). They proposed an optimized sample handling system that limited terrestrial contaminations during transportation between laboratory facilities and had the proper analytical sequence of examinations (Uesugi et al 2014a(Uesugi et al , 2019. The drawbacks of their research, however, were that these systems only suitable for µm-sized samples, and the original textures/structures of larger samples were readily lost when the sample was pressed onto an Au thin lm (Uesugi et al 2014a).…”
Section: Introductionmentioning
confidence: 99%